There is no outside of communication- metacommunication at the light of Derrida’s graphematic structure of communication - Mateus, Samuel (2020)
By claiming a general graphematic structure of every communication, Derrida builds a critique to traditional notions of unified or stable meaning, attacking the paradigm that sees in communication a phonocentric and self-sufficient attempt to seize meaning in an adequately, clear and understandable way from one point to the other. Anything functioning as means of communication must possess, in its iterability, the structure of writing. Indeed, communication is a kind of writing. In consequence, it may be examined according to the central notions of Différance, Supplement or Dissemination. The graphematic turn, in effect, opens the path to exam communication according to a de-centered paradigm. This chapter exploresthis assumption having in mind the relations between communication and metacommunication. We argue communication is always escaping us. It is permanently traveling along different paths of meaning happening between the lines. So, there is not beginning and no end. Anything more than communication would just be more communication. Metacommunication is, thus, the endless cycle of communication’s self-differentiation. It supplements communication and it is also supplemented by it.